Noncalcemic 20-hydroxyvitamin D3 inhibits human melanoma growth in in vitro and in vivo models - Skobowiat, Cezary (Oncotarget, 2016)
A novel pathway of vitamin D(3) (D(3)) metabolism, initiated by C20-hydroxylation of D(3) by CYP11A1, has been confirmed to operate in vivo. Its major product, 20(OH)D(3), exhibits antiproliferative activity in vitro comparable to that of 1,25(OH)(2)D(3), but is noncalcemic in mice and rats. To further characterize the antimelanoma activity of 20(OH)D(3), we tested its effect on colony formation of human melanoma cells in monolayer culture and anchorage-independent growth in soft agar. The migratory capabilities of the cells and cell-cell and cell-extracellular matrix interactions were also evaluated using transwell cell migration and spheroid toxicity assays. To assess the antimelanoma activity of 20(OH)D(3) in vivo, age-matched immunocompromised mice were subcutaneously implanted with luciferase-labelled SKMel-188 cells and were randomly assigned to be treated with either 20(OH)D(3) or vehicle (n=10 per group). Tumor size was measured with caliper and live bioimaging methods, and overall health condition expressed as a total body score scale. The following results were observed: (i) 20(OH)D(3) inhibited colony formation both in monolayer and soft agar conditions, (ii) 20(OH)D(3) inhibited melanoma cells in both transwell migration and spheroid toxicity assays, and (iii) 20(OH)D(3) inhibited melanoma tumor growth in immunocompromised mice without visible signs of toxicity. However, although the survival rate was 90% in both groups, the total body score was higher in the treatment group compared to control group (2.8 vs. 2.55). In conclusion, 20(OH)D(3), an endogenously produced secosteroid, is an excellent candidate for further preclinical testing as an antimelanoma agent.